Biosynthesis of Polysaccharides-Capped Selenium Nanoparticles Using Lactococcus lactis NZ9000 and Their Antioxidant and Anti-inflammatory Activities - Xu, Chunlan; Qiao, Lei; Ma, Li; Yan, Shuqi; Guo, Yu; Dou, Xina; Zhang, Baohua; Roman, Alexandra (Frontiers in Microbiology, 2019)
Lactococcus lactis (L. lactis) NZ9000 which has been genetically modified is the most commonly used host strain for nisin regulated gene expression. Selenium (Se) is an essential trace element in the diet of human and animals for maintenance of health and growth. Biosynthesized Se nanoparticles (SeNPs) using microorganism as vehicle possesses unique advantages including low cost, low toxicity and high bioavailability. The study was aimed to prepare novel functionalized SeNPs by L. lactis NZ9000 through eco-friendly and economic biotechnology methods. Moreover, its physicochemical characteristics, antioxidant and anti-inflammatory activities were investigated. L. lactis NZ9000 synthesized elemental red SeNPs when co-cultivated with sodium selenite under anaerobic conditions. Biosynthesized SeNPs by L. lactis NZ9000 were mainly capped with polysaccharides and significantly alleviated the increase of malondialdehyde (MDA) concentration, the decrease of glutathione peroxidase (GPx) and total superoxide dismutase (T-SOD) activity in porcine intestinal epithelial cells (IPEC-J2) challenged by hydrogen peroxide (H2O2). SeNPs also prevented H2O2-caused reduction of transepithelial electrical resistance (TEER) and increase of FITC-Dextran fluxes across IPEC-J2. Moreover, SeNPs attenuated the increase of reactive oxygen species (ROS), reduction of adenosine triphosphate (ATP) and mitochondrial membrane potential (MMP), and maintained intestinal epithelial permeability in IPEC-J2 cells exposed to H2O2. In addition, SeNPs pretreatment alleviated the cytotoxicity of Enterotoxigenic Escherichia coli (ETEC) K88 on IPEC-J2 cells and maintained intestinal epithelial barrier integrity by up-regulating the expression of Occludin and Claudin-1, and modulating inflammatory cytokines. Biosynthesized SeNPs by L. lactis NZ9000 would be a promising selenium supplement with antioxidant and anti-inflammatory activities.